Find the complete integral of partial differential equations z+xp-x2yq2-x3pq =0
f(x,y,z,p,q)=xpq+yq2-1=0"\\frac{dp}{\\frac{df}{dx}+p\\frac{df}{dz}}=\\frac{dq}{\\frac{df}{dy}+q\\frac{df}{dz}}=\\frac{dz}{-p\\frac{df}{dp}-q\\frac{df}{dq}}=\\frac{dx}{-\\frac{df}{dp}}=\\frac{dy}{-\\frac{df}{dq}}"
"\\frac{dp}{p-2xyq^2-3x^2pq+p}=\\frac{dq}{-x^2q^2+q}=\\frac{dz}{-p(x-x^3q)-q(2qyx^2-x^3p)}=\\frac{dx}{-x+x^3q}=\\frac{dy}{2qyx^2+x^3p}"
"\\frac{\\frac{dq}{q}}{1-qx^2}=\\frac{\\frac{dx}{x}}{x^2q-1}"
"\\frac{dq}{q}+ \\frac{dx}{x}=0"
ln(q)+ln(x)=a
qx=ea
q=ea/x
"\\frac{ \\frac{dp}{qp}+ \\frac{dy}{xp}}{\\frac{2}{q} - \\frac{2xyq}{p}-3x^2+ \\frac{2qyx}{p}+ x^2}=\\frac{ \\frac{dp}{qp}+ \\frac{dy}{xp}}{\\frac{2}{q} -2x^2}=0"
"\\frac{dp}{q}+ \\frac{dy}{x}=0"
"\\frac{p}{q}=- \\frac{y}{x} + b"
"\\frac{e^ap}{x}=- \\frac{y}{x} + b"
p=-yb/ea
dz=pdx+qdy=-yb/eadx+ea/xdy
z=-ybxea+eay/x+c=eayx (1/x2 - b)+c
Comments
Leave a comment